A brief experiential school counseling site supervisor training approach. Issue 2 (3rd July 2019) - Gruman, Diana H.; Purgason, Lucy L.
ABSTRACT: School counseling site supervisors report several challenges in obtaining the amount of supervision training they desire. In this article, we propose a brief supervision training approach, grounded in Experiential Learning Theory, designed to overcome time and resource constraints identified in the school counseling supervision literature. This training approach capitalizes on existing knowledge and skills while building ethical, multicultural, and relational competence in supervision. A rationale for the use of this training method, a review of the research-informed content, a description of three school-based supervision case studies, and pilot study data are provided along with recommendations for implementing the training in professional development contexts.